RESPONSIBILITY OF THE HEAD OF THE NATIONAL LAND AGENCY FOR THE ISSUANCE OF LAND OWNERSHIP CERTIFICATES WITH ADMINISTRATIVE LEGAL DEFECTS - Rahmat Febria Yuris; Amad Sudiro (Transpublika Publisher, 2023)
This paper delves into the responsibility of the head of the national land agency in handling administrative defects in Land Ownership Certificates (SHM) within the purview of administrative law. Employing a normative juridical research method, the study discerns that deficiencies in SHMs arise from various factors, whether intentional or unintentional. Such shortcomings may manifest in the data supplied by applicants during the certificate creation process or result from errors, both intentional and unintentional, in the identification of objects and subjects. Object-related discrepancies include inaccuracies in land mapping and measurement, while subject-related errors involve misinformation provided by applicants. This research aims to elucidate the origins of administrative defects in SHMs and underscores the pivotal role of the head of the national land agency in rectifying and preventing such issues. By understanding these factors, this study contributes to the broader discourse on enhancing the efficacy and reliability of land ownership certification processes, emphasizing the need for proactive measures to address and mitigate administrative defects.